Fronteira Brasil-Uruguai: interações espaciais, reivindicações territoriais e políticas públicas de desenvolvimento - Camilo Pereira Carneiro; Gabriel Silva Ribeiro; Letícia Eugênia Pereira de Morais (Confins)
Among the ten countries with which Brazil shares a border, it is with Uruguay that the ther is the strongest integration. The cooperation initiatives developed on this border serve as a model for all other Brazilian borders. In this sense, this paper brings a contemporary approach, based on Political Geography, of development public policies and spatial interactions in the twin cities on the Brazil-Uruguay border. Initially, the text addresses the historical formation of the Brazil-Uruguay border. Next, the article details the Uruguayan claims on the border and, finally, the main border integration initiatives are presented. In terms of methodology, it is a qualitative research, based on bibliographic and documentary analysis